Asas Pendidikan Ki Hajar Dewantara Dalam Cerita Rakyat Bengkulu - Asip, Muhammad; Dwidarti, Fera; Wisataone, Voettie; Likus (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
Folklore is a cultural heritage that holds many implicit and explicit meanings. The Ministry of Education and Culture in 1982 published a book entitled "Bengkulu Regional Folk Stories" with 20 stories in it. This study aims to determine the content of the educational principles of Ki Hajar Dewantara in Bengkulu folklore. This type of research uses the literature study method. Collecting research data using documentation study techniques. While the analysis of this research data using critical analysis techniques. Folklore that contains many values ​​of human life, including educational values. Ki Hajar Dewantara is an Indonesian education figure who initiated five principles of education for Indonesia. There are 20 stories from Bengkulu folklore which contain the educational principles of Ki Hajar Dewantara